Electronic tuning of two metals and colossal magnetoresistances in EuWO1+ xN2- x perovskites - Minghui Yang; Judith Oro-Sole; Anna Kusmartseva; Alba Fuertes; J. Paul Attfield (2010)
A remarkable electronic flexibility and colossal magnetoresistance effects have been discovered in the perovskite oxynitrides EuWO1+xN 2-x. Ammonolysis of Eu2W2O9 yields scheelite-type intermediates EuWO4-yNy with a very small degree of nitride substitution (y = 0.04) and then EuWO1+xN 2-x perovskites that show a wide range of compositions -0.16 < x < 0.46. The cubic lattice parameter varies linearly with x, but electron microscopy reveals a tetragonal superstructure. The previously unobserved x < 0 regime corresponds to oxidation of Eu (hole doping of the Eu:4f band), whereas x > 0 materials have chemical reduction of W (electron doping of the W:5d band). Hence, both the Eu and W oxidation states and the hole/electron doping are tuned by varying the O/N ratio. EuWO1+xN2-x phases order ferromagnetically at 12 K, and colossal magnetoresistances (CMR) are observed in the least doped (x = -0.04) sample. Distinct mechanisms for the hole and electron magnetotransport regimes are identified. © 2010 American Chemical Society.